Насичені жирні кислоти суцвіть чорнобривців прямостоячих сорту "Inka II Yellow" - Малюгіна, Олена Олександрівна; Смойловська, Галина Павлівна; Maliuhina, O. O.; Smoilovska, G. P. (My University, 2023)
Насичені жирні кислоти мають перспективи у якості допоміжних агентів, у тому числі при створенні лікарських засобів спрямованого транспорту. Особливу цікавіть викликає застосування природних сполук, які містяться у рослинній сировині, у складі сучасних лікарських засобів. Однією з перспективних рослин для розробки новітніх препаратів є чорнобривці. Метою роботи є визначення якісного складу та кількісного вмісту насичених жирних кислот у суцвіттях чорнобривців прямостоячих сорту «Inka II Yellow» методом газової хроматографії. У результаті поведеного дослідження визначено, що сумарний вміст насичених жирних кислот у досліджуваній сировині складає до 17,016±0,85%. Ідентифіковано п’ять насичених жирних кислот: арахінову, бегенову, міристинову, пальмітинову та стеаринову. Abstract. The lipophilic compounds such as fatty acids are an integral part of all plant cells. They have many important functions in human body cell. Modern studies demonstrated that fatty acids are not only an energy source, but also the structural parts of cell membrane. Saturated fatty acids are very perspective as excipients in pharmaceutical manufacturing, e.g., as part of the drug delivery systems. Research in recent years has focused on the possibility of using natural lipids as drug carriers, which is connected with their affinity to the cellular structures of the human body, which increases the ability of the drugs to overcome cell membranes and increase the therapeutic effect. Based on this, the possibility of using phytosomes as a more advanced form of plant compounds is considered. One of the promising plants for the creation of modern medicines are marigolds. Tagetes erecta L. is one of the most widespread and studied species of the genus Tagetes L. in the world. They contain a wide range of biologically active substances: flavonoids, carotenoids, tannins, organic acids, essential oils, vitamins and trace elements, etc. Extracts and individual compounds of marigolds have antimicrobial, wound-healing and anti-inflammatory effects. Tagetes erecta L. includes a large number of varieties that differ in morphological features and composition of biologically active substances. Intraspecific differences in the chemical composition of marigolds have been comprehensively studied. At the same time, less attention was paid to the study of the component composition and content of fatty acids of varieties of the genus Tagetes L. The aim of the work was studied the qualitative composition and quantitative content of saturated fatty acids in plant material of Tagetes erecta L. var. “Inka II Yellow”. Materials and Methods. Plant material was collected from July to September in Ukraine and dried by an oven at +60ºС to air-dry state. The content of unsaturated fatty acids in the raw materials was perform by gas chromatography. The quantitative content of fatty acids was determined by the method of internal normalization. The received data were statistically analyzed. Results and Discussion. The total contain of saturated fatty acids was determined up to 17,016±0,85%. There were identified to 5 saturated fatty acids such as palmitic acid, stearic acid, behenic acid, arachinic acid and myristic acid. The main saturated acids are stearic acid (4,117±0,205%) and palmitic acid (8,775±0,439). Stearic and palmitic acids are the structural components of the cell membrane and play the significant role in different physiological processes. These acids widely used in pharmaceutical and cosmetical manufacturing. Conclusion. We studied a qualitative composition and quantitative contain of saturated fatty acids of inflorescences of Tagetes erecta L. var. “Inka II Yellow”. The plant material contains up to 17,016±0,85% saturated fatty acids such as palmitic acid, stearic acid, behenic acid, arachinic acid and myristic acid. The main saturated acids are stearic acid and palmitic acid.
Saturated fatty acids of inflorescences of tagetes erecta l. Var. «Inka II Yellow»
Малюгіна О. О. - ORCID: 0000-0002-4909-4250; Смойловська Г. П. - ORCID: 0000-0002-6272-2012.
Keywords: fatty acids; African Marigold; Tagetes L.; жирні кислоти; чорнобривці прямостоячі